J.D.B. and the Maturing of Juvenile Confession Suppression Law - Guggenheim, Martin (2012)
The Supreme Court‘s decision in J.D.B. v. North Carolina in 2011 marks a watershed moment in the jurisprudence of juvenile rights. Addressing a question left open in Miranda v. Arizona more than four decades ago, the Court made clear in J.D.B. that a judicial determination of whether a minor suspect is in custody for Miranda purposes must take into account the age of the suspect because juveniles cannot be held to the same standard as adults. When one considers the broader context of the Court's criminal law jurisprudence of recent years, it is apparent that J.D.B. reflects the Court's willingness to extend, into new areas of criminal law, a recent line of cases that treats age eighteen as a central dividing line in how the Eighth Amendment regulates the sentences of capital punishment and life imprisonment without the possibility of parole. When one looks even further back into Supreme Court history, it is evident that J.D.B. marks a return to special protections for youth that characterized the Court's confession suppression caselaw more than half a century ago. This Article begins by looking back at juvenile confession suppression law in the half century preceding J.D.B. and examines the evolution of the doctrines applied in J.D.B. Part I demonstrates the special solicitude that the Court accorded juveniles half a century ago under the due process standard of voluntariness of statements and examines how and why this special protection was diluted in the ensuing decades. Part II focuses on J.D.B. itself. This section examines the new direction the Court took, the various ways in which J.D.B. diverged from the confession suppression jurisprudence of preceding years, and how the decision built upon the reasoning of recent Eighth Amendment caselaw. We also take a close look at the legislative facts in the J.D.B. decision and consider the implications of the Court having taken judicial notice of these legislative facts. Part III presents our views of the changes that J.D.B. demands of the criminal and juvenile justice systems. Part III.A shows that J.D.B.‘s restructuring of the standard for one aspect of Miranda analysis requires commensurate changes in all other aspects of the Miranda doctrine and other constitutional rules governing police interrogations. Part III.B presents our view that J.D.B., properly extended, requires that counsel be afforded to any minor suspect prior to and during any police interrogation